THE 5 STRATEGY TO ENHANCE INDONESIA’S AGRO-BASED INDUSTRY COMPETITIVENESS - Handito Hadi Joewono (Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
Within the period of 1995-2000, the international competitiveness of Indonesia agrobased industry sector had declined, down under the position of Thailand and China which are used as benchmark in this study. The decreasing of Indonesia domestic competitiveness within the same periode of time was more frustrated. This study was also find the linkage of Indonesia agro-based industry sector to Thailand and China. This study had an objective to analyse the competitiveness position of agro-based industry sector in Indonesia by analysing input-output in some Asia’s countries, especially between Indonesia, Thailand, and China. Specifically, the purpose of this study are : (1) Measuring the change of agro-based industry competitiveness in Indonesia, Thailand, and China; (2) Analysing the linkage between agro-based industry sector in Indonesia with the economy of Thailand and China; and (3) Calculating and analysing structural growth factors of agro-based industry sector in Indonesia, Thailand, and China. The analysis in this study used multilateral I-O model and data from Asian I-O Table 1995 and 2000 to get the competitiveness score through IIC (Index of International Competitiveness) and IDC (Index of Domestic Competitiveness), inter-country linkages, key sector and sources of growth through structural decomposition. This study founds that Indonesia had no primary source of growth in agro-based industry that could be used in the future development. Structural growth factor in agro-based industry sector in Indonesia did not have a pattern, while Thailand was supported by technological change factor, and China was supported by export expansion factor. Based on the above findings, this study come to some recommendations to increase Indonesia agro-based industry competitiveness as follows : (1) Developing agro-based industry as a key economic sector, (2) Increasing productivity, (3) Strengthening domestic competitiveness, (4) Increasing marketing-based competitiveness, (5) Developing technologybased economy.